Financial Product Design, Retail Investor Sophistication and Issuer Incentives: A Case Study. Issue 3 (5th September 2018) - Davis, Kevin
Abstract: Many financial products and securities marketed to retail investors involve design features that can make it difficult to understand the risk and return characteristics involved. This paper examines one such security, Convertible Preference Step Up Units (CPUs), issued in Australia by the US Masters Residential Property Fund (URF) at the end of 2017. It argues that an apparently relatively simple design masks significant complexity which would make risk assessment and fair pricing well beyond the capabilities of retail investors. Despite that, analysis of the security design and disclosure documents suggests that it would not fall foul of the financial product banning powers recommended for the Australian Securities and Investment Commission by the 2014 Australian Financial System Inquiry and in draft legislation as at mid 2018. This highlights the difficulties for effective financial consumer protection resulting from the mismatch between financial literacy levels and financial product design. Abstract : Convertible Preference Step Up Units, recently issued to retail investors in Australia, are examined in order to assess the suitability of their design and the likelihood of investors fully understanding the risk and return characteristics involved.